Legal Counseling on Contemporary Issues Regarding Simultaneous Village Head Elections in Sungai Selan Subdistrict - Rio Armanda Agustian (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bangka Belitung, 2022)
The Legal Counseling activity with the theme or title of Village Head Elections (Pilkades) which was carried out simultaneously in 8 (eight) villages in Sungai Selan Subdistrict, Central Bangka Regency, Bangka Belitung Islands Province is a program of the Faculty of Law, Universitas Bangka Belitung which is planned and implemented based on the situation and conditions where this is very important and useful, especially for institutions that must play an important role in providing advice and input for the community in Sungai Selan Subdistrict in the form of legal counseling activities that are useful and useful for the community. Sungai Selan Subdistrict is one of the sub-districts in Central Bangka Regency, which in general has an area of 789.74 square kilometers which consists of 1 (one) village, namely Sungai Selan Village and 12 (twelve) villages, namely Tanjungpura Village, Sungaiselan Atas Village, Ramadhon Village, Munggu Village, Lampur Village, Sarang Mandi Village, Keretak Village, Kerantai Village, Kemingking Village, Keretak Atas Village, Kerakas Village, Melabun Village. The villages are currently headed by a lurah who is appointed by the regent, recruited from a State Civil Apparatus (ASN). The kelurahan in Sungai Selan Subdistrict do not yet have autonomous rights like other existing villages. Kelurahan is an instrument of the local government of Central Bangka Regency that is tasked with carrying out its duties / functions as the government charged to it. Meanwhile, villages are headed by a village head (kades) whose appointment is made through village head elections (pilkades). Pilkades that occur in villages are similar to general elections, but are only required of all residents of the village concerned or who are domiciled in the village, and have fulfilled certain conditions in accordance with applicable laws and regulations. Since 2020, in Sungai Selan Subdistrict there has been 1 (one) lurah appointed or assigned to expedite the process of government activities at the sub-district level and an organizational structure of the sub-district has been formed to make it easier to provide services to the community. The implementation of legal counseling carried out at the Sungai Selan Subdistrict Office has a work program that hopes to provide understanding for the community such as understanding and understanding of various matters relating to the simultaneous village head elections in 8 (eight) villages in Sungai Selan Subdistrict while still prioritizing the Covid-19 security protocol during the activity.